Pressure inducing pH sensing on Fiber Bragg Grating / Habib Shawal - Shawal, Habib (2015)
This project presents system to continuously monitor pH by inducing pressure from electronics sensor to Fiber Bragg Grating (FBG). The problem with the current technology is that fiber optic chemical sensor need to undergo removal of cladding and sol-gel process which is not mass-manufacturer friendly and expensive. The objective of this project is to design alternative system to replace Fiber Optic Chemical Sensor. The project is divided into following scope (i) design the electronic gripper (ii) design servo driver circuit and (iii) characterize FBG response to gripper. To illustrate the functionality, we immersed electronic sensing in a solution and it will produce a change in parameters of output voltage. The output voltage is received by servo driver that produced voltage signal to electronic gripper and converted to pressure. The pressure is then applied to the Fiber Bragg Grating sensor. The output is detected by wavelength meter and analyzed by Agilent Vee. Results show a satisfactory regression factor of 0.99 in detecting the pH values. This project proves that electronics sensors can be combined with optical fiber sensing network to sense physical and chemical parameters in a single fiber.